The Role of Accounting Information Systems in the Industrial Revolution 4.0 - Nurul Dwi Tsoraya; Masduki Asbari; Dewiana Novitasari (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this research study is to provide a solution so that the role of accountants continues to exist in the era of the industrial revolution 4.0 by starting to learn computer programming so that they can adapt to existing changes. This study report used a descriptive qualitative method with data collection from articles on google or internet browsing. Because in recent years there have been various technological breakthroughs that produce new value in human life through the form of artificial intelligence. Business circles call this the core of the 4.0 industrial revolution. This condition has an impact on the role of humans, especially the accounting profession which will be replaced by the role of robots.